2021
DOI: 10.1186/s12883-021-02265-x
|View full text |Cite
|
Sign up to set email alerts
|

Low continuation of antipsychotic therapy in Parkinson disease – intolerance, ineffectiveness, or inertia?

Abstract: Background Antipsychotics are used in Parkinson disease (PD) to treat psychosis, mood, and behavioral disturbances. Commonly used antipsychotics differ substantially in their potential to worsen motor symptoms through dopaminergic receptor blockade. Recent real-world data on the use and continuation of antipsychotic therapy in PD are lacking. The objectives of this study are to (1) examine the continuation of overall and initial antipsychotic therapy in individuals with PD and (2) determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Exposure information was based on pharmacy dispensing and prescription claims and may not reflect actual patient-level use if patients are nonadherent to prescribed treatments. Another limitation is that discontinuation of antipsychotics is common in patients with PD [ 41 ], and although we evaluated mortality over time, the majority of patients had been lost to follow-up by 1 year after treatment initiation, limiting sample sizes in longer periods of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure information was based on pharmacy dispensing and prescription claims and may not reflect actual patient-level use if patients are nonadherent to prescribed treatments. Another limitation is that discontinuation of antipsychotics is common in patients with PD [ 41 ], and although we evaluated mortality over time, the majority of patients had been lost to follow-up by 1 year after treatment initiation, limiting sample sizes in longer periods of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A high discontinuation rate is not specific to pimavanserin. A retrospective cohort study of commercially-insured PD patients treated with antipsychotic medications found that the discontinuation rate after the first prescription was 39%, and after 6 months, the rate was highest for DRBDs and lowest for pimavanserin (23%) [8] . A retrospective chart review study reported a similar discontinuation rate of 36% for pimavanserin and 21% for quetiapine [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Haloperidol was the most commonly used drug (29%). More recently, a large database review in the United States, spanning 2001–2019, identified 3566 patients with PD treated with antipsychotics, 2452 were on quetiapine, 169 on aripiprazole, 462 on risperidone, and 304 olanzapine 33 . One hundred fifty-three had been treated with pimavanserin, which had become available in June 2016, and only 26 were treated with clozapine.…”
Section: Ethical Compliance Statementmentioning
confidence: 99%
“…More recently, a large database review in the United States, spanning 2001-2019, identified 3566 patients with PD treated with antipsychotics, 2452 were on quetiapine, 169 on aripiprazole, 462 on risperidone, and 304 olanzapine. 33 One hundred fifty-three had been treated with pimavanserin, which had become available in June 2016, and only 26 were treated with clozapine. A review spanning 2016-2019 of electronic medical records at a university hospital, of all patients with idiopathic PD and no primary psychiatric disorders, identified 2994 patients of whom 40 were on pimavanserin, 188 on quetiapine, 74 on both, and 11 taking "clozapine monotherapy or other antipsychotics."…”
Section: Ethical Compliance Statementmentioning
confidence: 99%